Pt‐Al2O3 interfaces in cofired ceramics for use in miniaturized neuroprosthetic implants. Issue 3 (16th September 2013) - Guenther, Thomas; Kong, Charlie; Lu, Hong; Svehla, Martin J; Lovell, Nigel H; Ruys, Andrew; Suaning, Gregg J
Abstract A core element to miniaturized, hermetic encapsulations for neuroprosthetic implants with high numbers of stimulation channels is the creation of electrical feedthroughs. Platinum (Pt) and alumina (Al2O3) are necessary to connect the sealed electronics to external components including electrode arrays that provide a neural interface function, as well as to sources of power or data. Combined with laser micro‐processing, high‐density feedthrough arrays were created with up to 2500 channels per cm2. The chemistry, micro structure, and crystallography of the Pt‐Al2O3 interface created by the cofiring of Pt particles and Al2O3 particulate in binder were studied by transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS) and selective area electron diffraction (SAED) to determine the nature of the Pt‐Al2O3 bond. While Pt‐Al2O3 interfaces only occurred in cases where the different grains were in distinct orientations where the crystal lattices matched, the addition of glass additives allowed for bonding nonmatching orientations by devitrification to form Pt‐glass‐Al2O3 interfaces. The conditions for the formation of both mechanisms were determined, and it was shown that higher order crystal planes than previously described can be matched. Analyzing the lattice matches in detail showed the ability of the material compound to compensate for mismatches by the formation of dislocations, out‐of‐angle matching, lattice distortion, and the existence of semi‐coherent interfaces in case of integer misfit ratios to create domain matching. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 500–507, 2014.